2020
DOI: 10.1177/1120700019896970
|View full text |Cite
|
Sign up to set email alerts
|

Wear and osteolysis outcomes for highly cross-linked polyethylene in primary total hip arthroplasty compared with conventional polyethylene: a 15- to 18-year single-centre follow-up study

Abstract: Background: Although highly positive results for wear reduction of highly cross-linked polyethylene (HXLPE) have been reported around the 10-year follow-up, the long-term result related to reoperation and wear-related survival is still an issue. Therefore, this study aimed to compare the follow-up results of a single manufacture’s polyethylene liner for >15 years in terms of survival and wear rate. Methods: This retrospective cohort study included 134 primary total hip arthroplasties (THAs) who were followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
(28 reference statements)
5
16
0
Order By: Relevance
“…The inserts examined in this study were made of conventional polyethylene. The wear rate detected in our study is comparable to the values found in other investigations [25,26]. The authors are aware that the use of crosslinked PE has significantly reduced the wear rate and osteolysis in general, regardless of the use of screws [26][27][28].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The inserts examined in this study were made of conventional polyethylene. The wear rate detected in our study is comparable to the values found in other investigations [25,26]. The authors are aware that the use of crosslinked PE has significantly reduced the wear rate and osteolysis in general, regardless of the use of screws [26][27][28].…”
Section: Discussionsupporting
confidence: 89%
“…The wear rate detected in our study is comparable to the values found in other investigations [25,26]. The authors are aware that the use of crosslinked PE has significantly reduced the wear rate and osteolysis in general, regardless of the use of screws [26][27][28]. Nevertheless, based on the results achieved in the present investigation, the authors recommend that, insofar as the primary stability of the implant allows it, the use of screws be done without.…”
Section: Discussionsupporting
confidence: 87%
“…Osteolysis of any size was noted among 9% of the XLPE hips versus 46% of the CPE hips (P < 0.001). Similar results with melted XLPE outperforming CPE with at least 15 years of follow-up were reported by Moon et al [8]. Since plain radiographs have a sensitivity close to 40% [9], osteolysis has been specifically assessed by Fukui et al [10] with computed tomography and 3D multiplanar reconstruction images.…”
Section: Long-term Wear Osteolysis and Survivorshipsupporting
confidence: 52%
“…Except age and comorbidity, other patient demographics factors, such as gender, body weight, BMI, UCLA activity score, alcohol, or steroid intake, but also liner thickness or femoral offset, had no influence on wear rates in that study. Conversely, Moon et al [8] failed to demonstrate any statistical correlation between wear and cup position.…”
Section: Risk Factors Of Wearmentioning
confidence: 93%
“…The Australian registry reported a hazard ratio of using noncrosslinked polyethylene of 3.02, and this discrepancy is further exaggerated in younger patients [17]. Using plain radiographs, several clinical studies reported decreased or no lysis associated with XLPE bearings after the first decade of surgery [4,6,22,26,35]. Linear wear of XLPE determined by Martell and Berdia [33] varied between 0.014 mm/year and 0.07 mm/year in these studies [4,22,25,26,39,43], which is less than the critical threshold for osteolysis of 0.05 mm/year [20] in most studies.…”
Section: Introductionmentioning
confidence: 99%